Diseño e implementación de una nueva experiencia de usuario para la aplicación Botón de Pánico - Riscanevo Vanegas, David Stiven; Pérez Peres, William Alejandro (Universidad Antonio Nariño, 2023)
Botón de Pánico mobile application is a tool for helping in the survivors rescue process in a natural disaster, in those times where network infrastructure collapses. This application has multiple functionalities which are supported on wireless communication technologies of the mobile device, specifically Bluetooth and Wi-Fi Direct. First version of Botón de Pánico application had several issues related to user experience. Although it met with its purpose, it was complicated for average user to interact with the application, and it intensified among a natural disaster, since in this context, it is expected that the user does not have the same reaction ability; this scenario was a threat due to the way the options of the application were displayed. Solution proposed by LACSER group was considered for the development of this project was to design a new user experience for its posterior implementation, thus, an easy-to-use application and stable operation was obtained. New user experience keeps the same functionalities with a new user interface and an optimal workflow focused on usability. It should be noted that this application is only available for Android mobile devices platform